Continuum of care for maternal, newborn, and child health in 17 sub-Saharan African countries - Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Richard Gyan Aboagye; Joshua Okyere; Eugene Budu; Sanni Yaya (BMC, 2022)
Abstract Background Given the intricate relationship between mothers and their children with the continuum of care, it is quintessential for their healthcare and interventions to be enhanced through a continuum of care approach. We examined the factors associated with the continuum of care for maternal, newborn, and child health in sub-Saharan Africa. Methods Data for the study were pooled from the Demographic and Health Surveys of 17 countries in sub-Saharan Africa. We extracted the data from the women's files in all 17 countries. We included 15,359 married and cohabiting women with the most recent children aged 12-23 months at the time of the survey in the study. Multivariable multilevel logistic regression analysis was performed to examine the factors associated with continuum of care. Results were presented as adjusted odds ratios (aORs) with their 95% confidence interval. Results Women whose partners had secondary or higher level of education [aOR = 1.52; 95%CI = 1.07, 2.16], those with health insurance [aOR = 1.64; 95%CI = 1.18, 2.30], those who decide alone on their healthcare [aOR = 1.38; 95%CI = 1.01, 1.89], those with joint healthcare decision [aOR = 1.33; 95%CI = 1.02, 1.74], those exposed to radio [aOR = 1.38; 95%CI = 1.06, 1.79], those who started antenatal care early [aOR = 1.88; 95%CI = 1.50, 2.36] and those in southern Africa [aOR = 7.02; 95%CI = 3.23, 15.27] had higher odds of completing the continuum of care. Conclusion We found that only 3.4% of women across the 17 sub-Saharan African countries included in this study completed all of the 11 maternal, newborn, and child health care interventions along the continuum of care. The factors that are associated with the maternal, newborn, and child health continuum of care include women's autonomy in decision-making, partners' level of education, health insurance coverage, early initiation of antenatal care, exposure to radio, and residing in Southern Africa. Problem with the distance to the facility lowered women's odds of completing the continuum of care. Governments and departments of health services across sub-Saharan African countries must leverage the radio to disseminate critical messages about the need to complete the continuum of care. Much commitment must be made toward advancing the autonomy of women. Health insurance coverage would have to be extended to reach all women to facilitate the completion of the continuum of care.